Two live births following orthotopic ovarian tissue autotransplantation: A case report of cycle monitoring and (modified) natural-cycle IVF in one patient - Nicole Francisca Klijn; Leoni Albertine Louwé; Gonneke Saskia Kirsten Pilgram; Lucia Alida Johanna van der Westerlaken (Elsevier, 2019)
Introduction: Ovarian tissue cryopreservation (OTC) is an option to preserve fertility. This article describes the effect of cycle monitoring on the chances of pregnancy following orthotopic ovarian tissue autotransplantation. Case presentation: A 32-year-old woman diagnosed with breast cancer underwent right-sided oophorectomy and OTC prior to chemotherapy. Three years later she was diagnosed with premature ovarian insufficiency and ovarian tissue chips were transplanted in the remaining ovary and a peritoneal window. Eight months after transplantation, activity was seen in the tissue placed in the peritoneal window. With a low natural chance of conception, modified natural-cycle (MNC) IVF was started by administration of a GnRH antagonist. Ovulation was triggered with hCG. One oocyte was retrieved by transvaginal ovum pick-up. After fertilization, a six-cell-stage embryo of good quality was transferred. This resulted in pregnancy and a healthy girl was born at 41 weeks. In the second monitored cycle after her delivery, a follicle was seen in the remaining ovary. Two weeks later a pregnancy test was positive and after an uncomplicated pregnancy a healthy boy was delivered spontaneously at 41 weeks. Conclusions: This case reports shows that MNC IVF conception after OTC is successful in patients with tissue partially placed in a peritoneal window. If the tissue placed in the peritoneal window becomes active, MNC IVF can be performed. If the tissue placed in the remaining ovary becomes active, natural conception should be pursued. Keywords: Fertility preservation, Ovarian tissue cryopreservation, Pregnancy, Cycle monitoring, IVF